1973
DOI: 10.1172/jci107181
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Experimental Diabetes Mellitus and Insulin Replacement on Hepatic Ultrastructure and Protein Synthesis

Abstract: A B S T R A C T The following study was conducted in order to define the specific alterations in hepatic ultrastructure responsible for the decrease in hepatic protein synthesis associated with experimental diabetes. Rats received intravenous alloxan (70 mg/kg) and 48 h later were either sacrificed or given insulin for 1, 2, 4, 6, or 24 h. Specimens for electron microscopic evaluation and morphometric analysis were taken from the same livers used to isolate ribosomes for measurement of in vitro protein synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 14 publications
3
29
0
1
Order By: Relevance
“…Other studies with perfused livers (6) or isolated hepatocytes (7) indicated an impaired secretion of proteins in diabetic rats. Such a defect may relate to the marked disruption and disorganization of the rough endoplasmic reticulum observed in liver of diabetic rats (8)(9)(10), as export proteins are synthesized almost exclusively on the rough endoplasmic reticulum (11).…”
mentioning
confidence: 99%
“…Other studies with perfused livers (6) or isolated hepatocytes (7) indicated an impaired secretion of proteins in diabetic rats. Such a defect may relate to the marked disruption and disorganization of the rough endoplasmic reticulum observed in liver of diabetic rats (8)(9)(10), as export proteins are synthesized almost exclusively on the rough endoplasmic reticulum (11).…”
mentioning
confidence: 99%
“…The hepatic protection in eviscerated animals 52 was almost identical to that observed with intraportal insulin therapy after portacaval shunt 10,11 and was indistinguishable from the hepatic protection provided by insulin in diabetic rats. 54 In hepatocyte tissue culture systems, many investigators have described analogous insulin effects. [55][56][57][58] The role of insulin in maintaining hepatocyte mitochondrial metabolism has also been emphasized.…”
Section: From Hormone Infusion Experimentsmentioning
confidence: 99%
“…Details of the preparation of liver samples for electron microscopy have been recently reported from this laboratory [2,3]: quantitative characterization of the RER was based on the methods of Loud [14] and Weibel [15].…”
Section: Morphometric Studiesmentioning
confidence: 99%
“…In contrast to the effect of diabetes on bound ribosomes, there was no change in protein synthetic activity of free polyribosomes isolated from livers of rats, 3, 7 or 28 days after induction of diabetes. Thus, the effect of any given degree of diabetes on hepatic protein synthesis appears to vary with the population of hepatic ribosomes being studied, and with duration of insulin deficiency.Key words: Insulin deficiency, protein synthesis, hepatic ribosomes, diabetic ribosomes.Previous studies from our laboratory have indicated that in vitro hepatic protein synthesis was decreased in rats with acute and severe experimental diabetes mellitus [1,2], and that this decrease in protein synthesis was accompanied by a marked loss and disruption of the hepatocyte rough endoplasmic reticulum [2]. Upon further analysis [3] it became clear that the decrease in total hepatic protein synthesis was limited to the bound polyribosome fraction.…”
mentioning
confidence: 91%
See 1 more Smart Citation